SENI TRADISIONAL BANTENGAN DI DUSUN BORO PANGGUNGREJO GONDANGLEGI MALANG - Faris, Amir; Khoyyum, Ahmad; Thoriqoh, Ita Uzzulaifatit; Nisak, Latifatun (LP3M IAI Al-Qolam, 2017)
Bantengan is an Indonesian folk performing art. Bantengan is a performance art that combines elements of martial arts, dances, kanuragan, music, and magical spell. Bantengan has spread in Indonesia, especially in East Java hinterland. One of them is in the hamlet of Boro Panggungrejo Gondanglegi Malang. However, there are some changes and shifts due to changes of time. One of the changes occurred in the